2018 Annual American Control Conference (ACC) 2018
DOI: 10.23919/acc.2018.8431613
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid PID control for transient performance improvement of motion systems with friction

Abstract: We present a novel reset control approach to improve transient performance of a PID-controlled motion system subject to friction. In particular, a reset integrator is applied to circumvent the depletion and refilling process of a linear integrator when the system overshoots the setpoint, thereby significantly reducing settling times. Moreover, robustness for unknown static friction levels is obtained. A hybrid closed-loop system formulation is derived, and stability follows from a discontinuous Lyapunov-like f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…The results presented in this paper provide a unified and comprehensive overview of the research accomplishments reported in [22,17,18,21,15] and the preliminary works [16,19]. As compared to those works we provide here a unified development, highlighting the importance of building hybrid models comprising logic variables to allow for the construction of smooth or Lipschitz Lyapunov functions, in addition to including a novel understanding of the exponential convergence properties of certain solutions in the Coulomb friction case.…”
Section: Introductionmentioning
confidence: 82%
See 4 more Smart Citations
“…The results presented in this paper provide a unified and comprehensive overview of the research accomplishments reported in [22,17,18,21,15] and the preliminary works [16,19]. As compared to those works we provide here a unified development, highlighting the importance of building hybrid models comprising logic variables to allow for the construction of smooth or Lipschitz Lyapunov functions, in addition to including a novel understanding of the exponential convergence properties of certain solutions in the Coulomb friction case.…”
Section: Introductionmentioning
confidence: 82%
“…A second reason for using coordinates x in (16) is that these provide a simplified representation of the sets where solutions are in the stick phase (the intervals where the top plots of Figures 4 and 5 are flat, namely the intervals where v ≡ 0) or in the slip phase (the time intervals associated to the speed bumps in the middle plots of Figures 4 and 5). In particular, we may define…”
Section: Stick and Slip Observed From Insightful Coordinatesmentioning
confidence: 99%
See 3 more Smart Citations